Morphological and Genetic Identification, and Population Structure of Kelah (Tor Tambroides) - Keong, Remmy Bun Poh (2006)
Tor tambroides, locally known as kelah, is one of the most sought after of the freshwater fishes in the country, both as food as well as a highly priced game fish. The identification of this fish into various groups and names is largely based on external features and colours. Thus, this study was undertaken to determine morphological differences, genetic variation and genetic relationships among three populations of Tor tambroides. Samples of kelah were taken from three locations, namely Pahang, Negeri Sembilan and Kelantan. A total of sixty three samples were used with weights ranging from 3.1 to 1800 g, total lengths ranging from 5.5 to 50.7 cm and standard lengths ranging from 4.2 to 40.0 cm.